Studi Kristologi Komparatif Personalitas Yesus Kristus dalam Perspektif Kristen dan Islam Menuju Dialog Interagama yang Konstruktif - Polii, Michael Fabio; Mawikere, Marde Christian Stenly (Jurnal Ilmiah Wahana Pendidikan, 2024)
The study of Christology navigates essential debates, with mainstream Christianity upholding the hypostatic union, affirming Jesus as both true God and true man. Scholars explore the coexistence of Jesus' divinity and humanity, articulated through christology from above and christology from below. The Islamic-Christian discourse often centers on Jesus' ontological nature. This research examines perceptions of the dogmatic structure in both faiths, utilizing a literature review to synthesize insights. Islamic Christology portrays Jesus as a human prophet (الْمَخْلُوق, Al-Mahkluq), distinct from the creator (الْخَالِق, Al-khaliq), while Christian Christology emphasizes Jesus' divinity, referencing him as the Word who is God himself (ϑεὸς ἦν ὁ λόγος, theos en ho Logos). Despite disparities, both share functional parallels in beliefs like the virgin birth, miracles, and eschatological anticipation. Encouraging critical discussions is paramount, fostering understanding, respect, and collaboration amidst differences. Recognizing doctrinal disparities while seeking common ground promotes peace, tolerance, and cross-religious understanding